2015
DOI: 10.2147/ott.s77378
|View full text |Cite
|
Sign up to set email alerts
|

The combination of preoperative serum C-reactive protein and carcinoembryonic antigen is a useful prognostic factor in patients with esophageal squamous cell carcinoma: a combined ROC analysis

Abstract: BackgroundThe prognostic value of inflammatory index in esophageal cancer (EC) has not been established. In the present study, therefore, we initially evaluated a novel prognostic system, named the COCC (COmbination of C-reactive protein [CRP] and carcinoembryonic antigen [CEA]), for making a prognosis in patients with esophageal squamous cell carcinoma (ESCC).MethodsA total of 327 patients with ESCC between January 2006 and December 2008 were included in this retrospective study. The COCC was calculated by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In addition, Gangopadhyay et al reported that cytokines, such as IL-1 α , IL-1 β , IL-6, and tumor necrosis factor- α were induced by treating Kupffer cells with CEA in vitro [ 21 ]. These elevations have been hypothesized to be a causative factor of several cancers and to be related to prognosis [ 22 , 23 ]. Taken together, these findings suggest a relationship between elevated serum IL-6 and CEA levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Gangopadhyay et al reported that cytokines, such as IL-1 α , IL-1 β , IL-6, and tumor necrosis factor- α were induced by treating Kupffer cells with CEA in vitro [ 21 ]. These elevations have been hypothesized to be a causative factor of several cancers and to be related to prognosis [ 22 , 23 ]. Taken together, these findings suggest a relationship between elevated serum IL-6 and CEA levels.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal cutoff values of D-dimer and albumin in our study were verified using Youden’s index (YI) from the receiver operating characteristic (ROC) curve for ESCC prediction. The survival status was inserted into the YI to define the cutoff value as described by Huang et al [ 22 ] and Liu et al [ 23 ]. A high level of preoperative plasma D-dimer was defined as ≥0.5 μg/mL, and a low level of preoperative serum albumin was defined as <43.8 g/L.…”
Section: Methodsmentioning
confidence: 99%
“… 13 , 14 Huang et al found that the combination of CRP and carcinoembryonic antigen was superior to CRP or CEA as a more precise prognostic factor in patients with esophageal carcinoma. 15 However, the role of combination of these inflammatory biomarkers in accessing GC prognosis is less well-known. We conducted a systematic literature review and surprisingly found that the significance of the combination of CRP and NLR (COC-NLR) for GC had not been studied yet.…”
Section: Introductionmentioning
confidence: 99%